Pemberdayaan Ekonomi Kreatif Karnaval Melalui Pelatihan Value Chain Untuk Mendukung Keunggulan Kompetitif - Sukarno, Hari; Khusna, Khanifatul; Muhsyi, Abdul; Subagio, N. Ari; Mirzania, Alif; Priyono, Agus; Fauziyyah, Salma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2023)
The variety of MSMEs in Indonesia makes this country rich in innovative products, including fashion products and shows packaged in carnivals. One organization that carries this concept is the Jember Fashion Carnaval Foundation (JFC). During the 16 years of its journey, JFC has made various achievements both at the national and international levels. JFC, the image of the city of Jember, was made the City of International Carnival by the Minister of Tourism. To increase JFC's value and bargaining products necessary to conduct value chain training. The value chain describes the activities in and around the organization and links them to the company's competitive strengths. To achieve the expected understanding of the value chain, the training strategy used the Asset Based Community Development approach. The activities began with observations and interviews, FGDs, and dissemination of material to JFC managers and activists. JFC managers and activities attended this activity. The result of this activity is improving the strategy for the JFC Foundation's competitive advantage. It is helpful to improve JFC's achievements at the national and international levels.